RESEARCH OF THERMO-GRAVITY CONVECTIVE PROCESSES IN LIQUID NUCLEUS AT HARDENING OF STEEL INGOTS - Ju. A. Samojlovich (Litʹë i Metallurgiâ, 2005)
The results of theoretical description of the melt moving in liquid ingot and in two-phase zone on the basis of numerical solution of problem are given.